The difficult assessment of the financial inclusion policies in India - Larquemin, Aurelie (International Journal of Social Sciences and Management, 2016)
Evidence of the importance of financial inclusion for economic growth and development are now well established and documented but little is known about the role institutions and policies can play and how institutional frameworks can support inclusive financial development. This paper is a case study on India, aiming to highlight the successes and difficulties encountered in the country financial development path. The results presented are based on an in-depth literature review and analysis of public secondary data. In the first section we discuss Indian initiatives for financial inclusion which started a decade ago, while in the second section we focus on more recent initiatives centered on digitization. Most of the oldest initiatives, through several changes and evolutions, have played a key role in expending financial inclusion in India, for instance the National Pension System or SHG groups. Public authorities are aware of the value of these schemes and have constantly tried to improve their features, expand their positive results and tackle identified issues. However they had too limited effects to allow the country to reach its goal towards financial inclusion. Moreover new technologies have appeared, opening new scope for financial inclusion, through innovative tools and schemes recently put in place by the public authorities. While we are lacking perspective to evaluate their effects, their preliminary results are encouraging and new schemes and regulations are being set up in this path. Int. J. Soc. Sci. Manage. Vol-3, issue-1: 31-37